GAGASAN RIFFAT HASAN TENTANG KRITIK GENDER ATAS HADIS MISOGINIS - Moh. Muhtador (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2017)
Riffat Hasan is one of the Muslim feminists against the strong patriarchal culture in his environment. Riffat Hasan's idea of ​​equality is a breath of fresh air for women who have been embraced by a growing patriarchal culture. As a Muslim feminist, Riffat hasan uses gender as an analysis to dismantle the construction of patriarchal culture wrapped with a religious message, especially the hadith of the prophet. The development of religious patriarchism is the result of interpretation of religious teachings that have the impression of gender bias (missoginis), gender bias interpretation model is one of the relations that shows the interaction of patriarchal culture with religion. The relationship forms a mutually supportive argument between religious teachings and patriarchal culture. So that both regions are understood as one-unit. But as a critical effort on the development of religious patriarchism, Riffat Hasan's idea of ​​gender can be used as a medium for finding ideological constructs, and the use of epistemology in the understanding of religious teachings. Thus, patriarchal religious and cultural relations are no longer seen as a whole that must be thoroughly replicated.